The lack of counselling and passively case detection affecting the occurrance of grade 2 disability in Sampang - Muhammad Kamal; Santi Martini (Jurnal Berkala Epidemiologi, 2015)
Leprosy is a chronic disease that attacks the skin, peripheral nerves, to other body organs which can cause permanent disability. Sampang is an area with the highest average prevalence rate (PR) of leprosy cases in the period 2010-2014 which has a proportion of level II disability of 13%, while the standard set is no more than 5%. The purpose of this study was to analyze the effect of health services on the incidence of leprosy level II disability. This type of research is observational-analytic research with a case-control design. This research was conducted in 8 working areas of the Public health centers (PHC) in Sampang District. The sample was Multi Basiler (MB) type of leprosy which consisted of 33 people with level II disabilities as a case group and 33 people with leprosy who had level 0 or level I disabilities as a control group. Sampling is done using a simple random sampling technique. Data analysis was performed simultaneously with the logistic regression test. The results showed that the passive case finding method (OR = 7,334; 95% CI = 1,643–32,739), very late diagnosis time (OR = 15,267; 95% CI = 1,447–161,071), lack of Prevention of Disability (POD) (OR = 7,016; 95 % CI = 1,574–31,274) and lack of counseling (OR = 9,154; 95% CI = 1,786–46,906) influenced the incidence of level II leprosy disability. The conclusion of this study is that the case-finding method, diagnosis time, POD, and counseling affect the incidence of level II leprosy disability in patients. It is recommended to actively increase case finding and improve counseling activities.